Predictors of Suicidal Thoughts and Attempts among School-Going Thai Adolescents: A Sex-Specific Structural Equation Modelling Analysis - Dadras, Omid (Springer Science and Business Media LLC, 2025)
Adolescent suicide is a growing public health concern in Thailand. Identifying predictors of suicidal behaviors is essential for targeted prevention strategies. Using Structural Equation Modeling, this study explores the predictors of suicidal thoughts and attempts among a sample of 5657 Thai adolescents in grades 7-12, typically representing the age group 13-17 years, with nearly equal proportions of males (47%) and females (53%) participants. Data from the Thailand Global School-based Student Health Survey (GSHS) 2021 were analyzed. Explanatory Factor Analysis (EFA) identified key constructs, followed by SEM stratified by sex to examine relationships between constructs and suicidal behaviors. Reliability and validity were assessed using Cronbach's α and SEM fit indices. EFA identified five constructs: current substance use, history of violence, experiences of bullying, parental awareness, and poor mental health. SEM revealed poor mental health as a significant predictor for both sexes. Substance use, experiences of bullying, and a history of violence predicted suicidal behaviors in females. Parental vigilance was only a protective factor for males. The findings underscore the importance of gender-specific interventions and comprehensive mental health support to address the unique vulnerabilities of Thai adolescents, reducing suicidal thoughts and attempts.